Making corporate self-regulation effective in developing countries - David Graham; Ngaire Woods (University of Oxford, Global Economic Governance Programme (GEG), 2005)
Self-regulation by multinational corporations of social/ environmental impacts has been advocated as a solution to the regulatory capacity problems faced by developing states. Market pressures can provide incentives for firms to implement codes and standards, but rely on widely available information about corporate behaviour. Voluntary schemes attempt to provide reliable, standardized reporting of information. But government action - in the North and South - remains vital to effective regulation, by setting social goals and upholding the freedom of civil society actors to organize and mobilize. International organizations and legal instruments may be able to assist developing country governments in fulfilling these roles.
Keywords: 330